PEMANFAATAN FAMILI ZINGIBERACEAE SEBAGAI OBAT TRADISIONAL DI DESA TIREMENGGAL KABUPATEN GRESIK - IRMATUL LAILI; Sitti Nur Ilmiah; Slamet Ifandi (Jurnal Matematika dan Sains (JMS), 2022)
The Zingiberaceae tribe is a plant that has the potential as a traditional medicine that is widely used by the community in curing various diseases. This study aims to determine the diversity and utilization of Zingiberaceae tribal plants as traditional medicine in Tiremenggal village. The method used in this study is a descriptive method with qualitative and quantitative approaches, to determine the analysis of the value of community use of medicinal plants analyzed by the ICS (Indexs of Cultural Significance) method. There are 5 families of Zingiberaceae which are used by the people of Tiremenggal village, namely ginger, turmeric, galangal, kencur and temulawak. The plant that is often used by the community as a treatment is ginger. The part that is used as medicine is the rhizome, which is mostly used to treat stomach pain, taken by mouth. Medicinal plants that are used by the community traditionally are still used today even though the preparation is done simply.